f(x)=x^3 and g(x)=x+4

g(1) = 1+4 = 5

so, f(g(1)) = f(5) = 5^3 = 125

f(1) = 1^3 = 1

so, g(f(1)) = g(1) = 1+4 = 5

f(g(x)) = (x+4)^3 = x^3 + 12x^2 + 48x + 64

g(f(x)) = x^3 + 4

f(t) = t^3

g(t) = t + 4

last one was a typo its f(t)g(t)

Ok, then it's

(t^3)(t+4) = t^4 + 4t^3

i have another question g(x)= X^2+9x+3. find g(2+h), g(2), and g(2+h)-g(2)

g(2+h) = g(h+2) = (h+2)^2 + 9(h+2) + 3

= h^2 + 4h + 4 + 9h + 18 + 3

= h^2 + 13h + 25

g(2) = 2^2 + 9(2) + 3

= 4 + 18 + 3

= 25

g(2+h) - g(2) = h^2 + 13h

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up